Is cognitive impairment associated with antipsychotic dose and anticholinergic equivalent loads in first-episode psychosis?. Issue 13 (14th January 2018) - Ballesteros, Alejandro; Sánchez-Torres, Ana M.; López-Ilundain, Jose M.; Cabrera, Bibiana; Lobo, Antonio; González-Pinto, Ana M.; Díaz-Caneja, Covadonga; Corripio, Iluminada; Vieta, Eduard; de la Serna, Elena; Bobes, Julio; Usall, Judith; et al.
Abstract: Background: Cognitive deficits are a core feature of early stages in schizophrenia. However, the extent to which antipsychotic (AP) have a deleterious effect on cognitive performance remains under debate. We aim to investigate whether anticholinergic loadings and dose of AP drugs in first episode of psychosis (FEP) in advanced phase of remission are associated with cognitive impairment and the differences between premorbid intellectual quotient (IQ) subgroups. Methods: Two hundred and sixty-six patients participated. The primary outcomes were cognitive dimensions, dopaminergic/anticholinergic load of AP [in chlorpromazine equivalents (Eq-CPZ) and the Anticholinergic Risk Scale (ARS), respectively]. Results: Impairments in processing speed, verbal memory and global cognition were significantly associated with high Eq-CPZ and verbal impairment with high ARS score. Moreover, this effect was higher in the low IQ subgroup. Conclusions: Clinicians should be aware of the potential cognitive impairment associated with AP in advanced remission FEP, particularly in lower premorbid IQ patients.